Wujud Adaptasi Masyarakat Kalibiru dalam Pengembangan Ekowisata - Kaharuddin Kaharuddin (Jurnal Pariwisata Terapan, 2020)
Ecotourism development by local communities around the forest has obstacles related the differences between farming and tourism working style. The problem's related the ability of the community to adapt. This study is aimed to describe the types of obstacles, strategies and the form of adaptation of the Kalibiru community in developing ecotourism in the protected forest. Data collection uses in-depth interviews (indept interview), focused interviews, direct observation, and document review. The results showed the ability of the Kalibiru community to adapt of ecotourism. Various obstacles experienced at each stage of tourism development can be overcome through persuasive strategies. The adaptation can be seen in the changes individual behavior, the structure and rules of the HKm institution, and settings of labor and working time at the household level. Keywords. Adaptation, ecotourism, local communities